Pengaruh Kompetensi Spiritual dengan Disiplin Siswa di Lingkungan Sekolah (Studi Kasus MTs Darul Qudwah Tegal) - Nadhifah Mizana Al-Azwi; Siti Rahmah (Fakultas Tarbiyah Institut Ilmu Al-Qur'an (IIQ) Jakarta, Indonesia, 2019)
Education is essentially a conscious effort to develop the personality that is in a person to be better, smarter, creative and innovative. Spiritual competence is character and attitude which is the deepest part of awareness in a person related to which not only recognizes the awareness of fixed values but is also creative in finding new values. Discipline is a process of training the mind and character of children gradually so that they become someone who has self-control and is useful for the community. This study aims to determine whether there is a influence between Spiritual competence and student discipline in the MTs Darul Qudwah Tegal School environment. This type of research is correlation research, which explains whether there is a influence between variable X as an independent or independent variable (Spiritual Competence) and Y as a dependent variable (Discipline). The population in this study were some students of MTs Darul Qudwah Tegal, totaling 63 students. In this study the sampling technique used was purposive sampling technique, namely sampling data. Based on this research, spiritual competence variable (X) is obtained which influences discipline variable (Y) where there is a positive influence meaning higher variable X and higher Y variable.